Rank of green building material criteria based on the three pillars of sustainability using the hybrid multi criteria decision making method - Khoshnava, S.; Rostami, R.; Valipour, A.; Ismail, Mohamed; Rahmat, A. (Elsevier, 2018)
A green building material (GBM) is an ecological, health-promoting, recycled, or high-performance building material that impacts the material selection to cover all three pillars (3Ps) of sustainability. The absence of clear instructions for GBMs and the difficulty of precision adjustments of GBM criteria with 3Ps sustainability make GBM selection a challenge. In addition, the consideration of all sustainability factors in GBM selection is a multi-criteria decision problem that requires mathematical techniques such as the multi criteria decision making (MCDM) method. This study applies a hybrid MCDM methodology to resolve multiple incompatible and conflicting GBM criteria to align with 3Ps sustainability. The Decision-Making Trial and Evaluation Laboratory (DEMATEL) was used to analyze the efficacy of and interrelationship between GBM criteria. This tool is a hybrid model using fuzzy analytic network process (FANP) for aligning and ranking GBM criteria based on 3Ps sustainability. Additionally, the study inspects four groups of professionals in Malaysia who involved in GBM selection and modified one of the oldest GBM criteria models considering the criteria identified from a comprehensive literature review. The results show that the relationship between GBMs and sustainability criteria are different based on the separate 3Ps of sustainability. The evaluation and results provide a valuable reference for building professionals to enhance sustainable construction through green materials.